Habitus, Modal, dan Arena Warga Desa Belanti Siam dalam pusaran Food Estate - May Linda Sari; Tahan Mentria Cambah; Helen Melenia (Unit Penerbitan Informasi dan Teknologi Sekolah Tinggi Teologi Gereja Kalimantan Evangelis (STT GKE), 2022)
Since 2019, the government has implemented a national program to build a national-scale food barn known as the Food Estate. This food estate area is being developed in the provinces of North Sumatra and Central Kalimantan. Substantially, the purpose of this food estate program is very large, namely to become a place for the development of food diversification and extensification that will ensure the availability of food to meet the needs of the community for a long time and is sustainable. In Central Kalimantan province, food estate is being developed in two districts, namely Pulang Pisau and Kapuas districts. Of course, this program is expected to bring satisfactory results as expected. Not only that but it is also expected to have an impact on the lives of the people living in the program area. One of the interesting areas to study is Belanti Siam village, Pandih Batu sub-district, Pulang Pisau district, and Central Kalimantan. In this area, most of the population has been sucked into farmer groups who are developing hybrid rice cultivation and have also enjoyed the harvest through the food estate program. This study is an attempt to examine the extent to which this program has a social and cultural impact on the Belanti Siam village community. The research was carried out from February-June 2022 using a qualitative method. The data were then analyzed using Bourdieu's theory of social practice theory, resulting in 3 research findings, namely: first, the Belanti Siam village community experienced social and economic changes in the form of capacity building and quality of life. Second, the food estate has a positive impact on the social life of the local community, especially in the economic sector and improving road infrastructure. And third, the community still maintains the values ​​of local wisdom in terms of planting and harvesting.